Detecting Changes in Soil Fertility Properties Using Multispectral UAV Images and Machine Learning in Central Peru - Enriquez Pinedo, Lucia Carolina; Ortega Quispe, Kevin Abner; Ccopi Trucios, Dennis; Rios Chavarria, Claudia Sofía; Urquizo Barrera, Julio; Patricio Rosales, Solanch Rosy; Alejandro Mendez, Lidiana Rene; Oliva Cruz, Manuel; Barboza Castillo, Elgar; Pizarro Carcausto , Samuel Edwin (MDPI, 2025)
Remote sensing is essential in precision agriculture as this approach provides high-resolution information on the soil's physical and chemical parameters for detailed decision making. Globally, technologies such as remote sensing and machine learning are increasingly being used to infer these parameters. This study evaluates soil fertility changes and compares them with previous fertilization inputs using high-resolution multispectral imagery and in situ measurements. A UAV-captured image was used to predict the spatial distribution of soil parameters, generating fourteen spectral indices and a digital surface model (DSM) from 103 soil plots across 49.83 hectares. Machine learning algorithms, including classification and regression trees (CART) and random forest (RF), modeled the soil parameters (N-ppm, P-ppm, K-ppm, OM%, and EC-mS/m). The RF model outperformed others, with R² values of 72% for N, 83% for P, 87% for K, 85% for OM, and 70% for EC in 2023. Significant spatiotemporal variations were observed between 2022 and 2023, including an increase in P (14.87 ppm) and a reduction in EC (-0.954 mS/m). High-resolution UAV imagery combined with machine learning proved highly effective for monitoring soil fertility. This approach, tailored to the Peruvian Andes, integrates spectral indices and field-collected data, offering innovative tools to optimize fertilization practices, address soil management challenges, and merge modern technology with traditional methods for sustainable agricultural practices.